Production of enzymatic hydrolysates with in vitro antioxidant, antihypertensive, and antidiabetic properties from proteins derived from Arthrospira platensis. (January 2023) - Villaró, Silvia; Jiménez-Márquez, Sergio; Musari, Evan; Bermejo, Ruperto; Lafarga, Tomás
Graphical abstract: Highlights: The microalga A. platensis BEA 005B was produced using large raceway reactors. The biomass was rich in proteins (58.1%) and carbohydrates (25.6%). Approximately 90% of the proteins were recovered after isoelectric precipitation. The protein isolate was hydrolysed in vitro using papain, ficin, pepsin or Alcalase. The hydrolysates showed in vitro antidiabetic and antihypertensive properties. Abstract: The microalga Arthrospira platensis BEA 005B was produced using 80 m 2 (9 m 3 ) raceway photobioreactors achieving a biomass productivity of 28.2 g·m −2 ·day −1 when operating the reactors in semi-continuous mode (0.33 day −1 ). The produced biomass was rich in proteins (58.1 g·100 g −1 ) and carbohydrates (25.6 g·100 g −1 ); the content of phycocyanins and allophycocyanins was 115.4 and 36.9 mg·g −1, respectively. Ultrasounds and high-pressure homogenisation allowed recovering approximately 90% of the initial protein content of the biomass; however, the energetic requirements of the former (∼100 kJ·kg −1 ) were significantly lower than those of high-pressure homogenisation (∼200 kJ·kg −1 ). An in silico analysis revealed that papain and ficin would allow releasing a large number of bioactive peptides with antioxidant, antihypertensive (ACE-I and renin), and antidiabetic (DPP-IV, α-amylase, and α-glucosidase) properties. Both were assessed in vitro together with Alcalase and pepsin leading to the generation of enzymatic hydrolysates with in vitro bioactivity.